Myocardial Protecting Role of Glutamine in Patients with Low Ejection Fraction Undergoing Elective On-Pump Coronary Artery Bypass Graft Surgery - Parmana, I Made Adi; Boom, Cindy Elfira; Rachmadi, Lisnawati; Hanafy, Dudy Arman; Widyastuti, Yunita; Mansyur, Muchtaruddin; Siswanto, Bambang Budi (Dove Medical Press Ltd, 2022)
Purpose: Myocardial injury due to on-pump coronary artery bypass grafting (CABG) in patients with low ejection fraction (EF) is associated with poor outcomes. This study determines whether intravenous glutamine could protect the myocardium during on-pump CABG in patients with low EF. Materials and Methods: This was a double-blind, randomized controlled trial to assess glutamine as a myocardial protector during on-pump CABG in patients with left ventricle EF of 31–50, conducted from January to October 2021. Patients in the glutamine group (n = 30) received 0.5 g/kg of 20 glutamine solution diluted with 0.9 NaCl up to 500 mL in total volume over a period of 24 hours. Patients in the control group (n = 30) received 0.9 NaCl over the same period. The primary outcomes were plasma troponin I and plasma glutamine levels. Secondary outcomes included α-ketoglutarate (α-KG) levels and histopathology scoring of the right atrial appendage tissue, plasma lactate levels, hemodynamic measurement, and morbidity. Results: Twenty-nine patients from each group (58 in total) were included in the analysis. Plasma troponin I levels at 6 and 24 hours after cardiopulmonary bypass (CPB) were significantly lower in the glutamine than the control group (mean 3.43 ± 1.51 ng/mL vs mean 4.41 ± 1.89 ng/mL; p = 0.034; median 3.08 ng/mL min–max: 1.30–6.59 vs median 3.77 ng/mL min–max: 0.00–36.53; p = 0.038, respectively). Plasma glutamine levels at 24 hours after CPB were significantly higher in the glutamine than the control group (mean 935.42 ± 319.10 μmol/L vs mean 634.79 ± 243.89 μmol/L, p = 0.001). Plasma lactate levels at 6 and 24 hours after CPB were significantly lower in the glutamine than the control group (median 5.30 mmol/L min-max: 1.20–9.50 vs median 5.70 mmol/L min-max: 2.80–11.30, p = 0.042; mean 2.08 ± 0.67 mmol/L vs mean 2.46 ± 0.69 mmol/L, p = 0.044, respectively). Myocardial injury score was significantly lower in the glutamine than the control group (mean 1.30 ± 0.24 vs mean 1.48 ± 0.26, p = 0.011). Conclusion: Perioperative administration of 0.5 g/kg intravenous glutamine solution over the period of 24 hours has myocardial protection effect in patients with low EF who undergo elective on-pump CABG. © 2022 Parmana et al.